Business Roundtable Insights on the Current Challenges Facing the Project Profession - Wong, Jun; Young, William; Alex, Trevor; Stockman, Hieu-Duc (Asian Business Review, 2020)
The purpose of this paper was to capture an industry perspective on the current project and project management challenges. Based on four Business Roundtable meetings held in Melbourne over a year, concluding mid-2019, the paper attempts to distill the erudite insights of participants into contemporary business challenges and solutions. The predominant theme of the meetings was dealing with business change and its rate of the rollout. There has been a distinct industry shift in expectation replacing major business transformations with a new continuous delivery paradigm. There was an agreement regarding many of the adaptation measures needed to meet this new challenge.